Utilizing Mentimeter as a Formative Assessment Medium to Understand Arabic Texts in Higher Education - Sa`diyah, Halimatus; Mubasyiroh, Mubasyiroh; Wala Binti Fahad al-Sobait (Jurnal Al Bayan : Jurnal Jurusan Pendidikan Bahasa Arab, 2025)
The utilization of technology in the field of education is rapidly advancing, including for foreign language learning such as Arabic. One of the tools currently employed is Mentimeter, an interactive platform that enables educators to create real-time tests and assessments. The aim of this article was to explore students' perceptions regarding the use of Mentimeter as a formative assessment tool to enhance their understanding of Arabic texts. This research employed a quantitative descriptive method with an evaluative basis. Data collection involved surveys using Likert scales. The study participants consisted of 80 Psychology students who are engaged in intensive Arabic language learning. Data analysis indicated that the majority of students respond positively to the use of Mentimeter as a formative assessment tool. They expressed that employing Mentimeter results in greater learning motivation and enhances their comprehension of Arabic texts. These findings contributed to understanding the effectiveness of Mentimeter in the context of Arabic language learning at the student level and underscore the importance of integrating technology in innovative learning practices.